Design and Development of UI/UX HRIS Application for Human Resource Management at PT Kreatif System Indonesia - Widyastuti, Hilda; Haikal, M. Taufiq (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
The rapid shift toward digital business requires organizations to implement integrated Human Resource Management (HRM) systems to reduce inefficiencies caused by manual processes. At PT Kreatif System Indonesia, the lack of integration between the fingerprint attendance system and core HR functions resulted in fragmented data, higher human error risk, and reduced decision-making accuracy. This study focused exclusively on PT Kreatif System Indonesia to address its internal operational challenges. The research aimed to design a consistent, easy-to-use, and memorable UI/UX based on Material Design principles and validate it through comprehensive usability evaluation. Interface consistency was emphasized to reduce cognitive load, improve recognition, and support smooth task execution across different user skill levels. The Prototyping development model enabled iterative refinements through continuous user feedback. Usability was evaluated using Task Completion Rate (TCR), Time-Based Efficiency (TBE), and the System Usability Scale (SUS). The developed HRIS successfully integrated all targeted modules. Initial testing achieved a TCR of 87.85% and a TBE of 0.0878 goals/second, which improved to 93.45% and 0.1258 goals/second after UI/UX enhancements. A SUS score of 74.42 indicates that the system is acceptable and well received. These results confirm that consistent UI/UX design significantly enhances HRIS effectiveness, efficiency, and usability.